Drivers of short-term variability in phytoplankton production in an embayment of the southern Benguela upwelling system: an observational and modelling study - Burger, Jessica (Department of Oceanography, 2019)
In the southern Benguela upwelling system (SBUS), the wind-driven supply of nutrient-rich water from depth sustains elevated levels of primary productivity. St Helena Bay (SHB), a coastal embayment in the SBUS positioned north of an upwelling centre, is an area of water mass retention. In addition to supporting 40-50% of total SBUS productivity, SHB often experiences harmful algal blooms (HABs) and hypoxic conditions that are difficult to predict given the high sub-seasonal variability that characterises this region. To better understand this variability, net primary production (NPP), nitrate and ammonium uptake, and phytoplankton community composition were measured for ten days during the upwelling season at an anchor station in SHB. A period of active upwelling (days 1-5) was followed by one of relaxation (day 6-10), together constituting an “upwelling cycle”. During upwelling, the mixed layer was deeper than the euphotic zone and phytoplankton were light-limited, evidenced by high ambient nutrient concentrations and relatively low rates of NPP and nitrate uptake. During relaxation, water column stratification increased, restricting phytoplankton production to a shallow, well-lit surface layer in which nitrate was exhausted after three days. The subsequent decline in NPP and nitrate uptake rates confirms that nutrient availability succeeded light as the ultimate control on productivity during the relaxation phase. Of the three phytoplankton size classes investigated (0.7-2.7 µm, 2.7-10 µm, >10 µm), the 2.7-10 µm fraction contributed most to the measured increases in biomass and nutrient uptake rates. This was unexpected given that large (>10 µm) diatoms typically dominate in upwelling systems; however, the 2.7-10 µm size fraction achieved a faster growth rate and sustained it for longer than the other size classes. The success of this size fraction may be partly due to a capacity for luxury nitrate uptake, evidenced by a low biomass C:N ratio and a nitrate uptake rate that was decoupled from NPP. Throughout the experiment, the phytoplankton community comprised mainly Chaetoceros spp. and Skeletonema costatum. These diatoms occupy a large size range (2-80 µm), although it is likely that they mainly occurred in the 2.7-10 µm size class during the experiment. They also produce resting spores that may provide a selective advantage during seeding in highly variable upwelling systems, increasing their chances of proliferating when conditions become favourable. Once the water column stratified, the phytoplankton community diversified, with dinoflagellates and the large diatom, Coscinodiscus gigas (200-500 µm), becoming more abundant. The contribution of C. gigas to biomass and productivity was not fully accounted for in the measurements because collected seawater was screened (200 µm mesh) prior to incubation. However, a simple N₃P₃ ecological model parameterized with the observations suggests that their contribution would have been minimal. The hydrographic data indicate that another upwelling cycle commenced by day 10 of the experiment. This likely prevented the further proliferation of dinoflagellates, some of which are HAB species, that may have succeeded the small diatoms given a longer period of quiescence. One implication of this is that understanding the rapid cycling between light and nutrient limitation, as induced by an actively upwelling versus stratified water column, may advance our capacity to predict the occurrence of HABs in SHB.